2020
DOI: 10.1021/acs.jpca.0c06838
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation of Isoxazole: A Photoelectron Imaging Study

Abstract: We report a photoelectron imaging study of gas-phase deprotonation of isoxazole in which spectroscopic data are compared to the results of electronic structure calculations for the anion products corresponding to each of three possible deprotonation sites. The observed photoelectron spectra are assigned to a mixture of the anion isomers. Deprotonation at the most acidic (C5) and the least acidic (C4) positions yields the respective C5- and C4-isoxazolide anions, while the reaction at the intermediate-acidity C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…This approach to modeling photoelectron spectra has been previously tested on other systems. 17,28,29 The VDEs and the full widths at half-maxima (FWHM) of the Gaussian parts of the four WSG functions are included in the table insets in Figure 2b,c. The parameters of WSG(1) and WSG(2) were adjusted independently in both cases.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This approach to modeling photoelectron spectra has been previously tested on other systems. 17,28,29 The VDEs and the full widths at half-maxima (FWHM) of the Gaussian parts of the four WSG functions are included in the table insets in Figure 2b,c. The parameters of WSG(1) and WSG(2) were adjusted independently in both cases.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Although the final state in molecular anion photodetachment is always a superposition of partial waves with different l values, in the absence of detailed information about the partial-wave composition, the above scaling function is most appropriate at low energy, where this effect is most pronounced. This approach to modeling photoelectron spectra has been previously tested on other systems. ,, …”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we modeled congested bands using the Wigner-scaled Gaussian (WSG) function The Gaussian part of WSG approximates the Franck–Condon envelope peaking at the transition’s VDE, while ( h ν – eBE) P = ε P multiplied by the Heaviside function Θ­( h ν – eBE) is a Wigner prefactor accounting for the eKE-dependent scaling of the electronic cross section. With P = l + 1/2, the electronic term corresponds to the Wigner threshold law, , σ ∝ ε l +1/2 , where l is the orbital angular momentum quantum number of the outgoing electron.…”
Section: Spectral Modeling and Discussionmentioning
confidence: 99%
“…39 Previous microwave spectroscopy, 40 infrared (IR) spectroscopy, 41,42 and ab initio calculations 41 reported the geometrical and vibrational parameters of neutral isoxazole in its ground electronic state. Gas-phase photoelectron imaging study revealed that the hydrogen (C5H) adjacent to ring O is more acidic than the hydrogen (C3H) close to skeletal N. 43 Past microwave investigation of the isoxazole−argon (iso- xazole−Ar) complex showed that the nonpolar Ar ligand binds to the aromatic π electron cloud and slightly moves to the N− O bond because of the exchange repulsion forces. 44 However, changing the solvent to polar aprotic CO causes a substantial modification of the solvent-binding motif.…”
Section: Introductionmentioning
confidence: 99%